Opportunities and Challenges: The Financial Impact of Net-Metering on the Mexico Area Branch Office of Pampanga I Electric Cooperative, Inc. - Pacurza, John Alvie; Manalang, Marion Angelo; Manalili, Nelson S; Manaloto, Carl Jonash M; Medina, Russel Roel T; Bulanan, Eldren V; Tiria, Genesis C (Universitas Komputer Indonesia, 2027)
This study investigated the present opportunities and challenges about the financial impact of the operation and implementation of the Net-metering program on the Mexico area branch office of (Pampanga I Electric Cooperative, Inc.) PELCO 1, derived from the quantitative and qualitative data from responses of the involved participants. It aims to identify the level of awareness and experience of both regular and net-metered consumers, assess the operation and financial implications of the program, identify the associated operational and regulatory challenges, and provide policy recommendations. The key themes identified include technological advances in billing and monitoring, cooperative sustainability with solar adoption, clearer regulations and sanctions, negative balances and potential financial risks, and importance of proactive guidance from PELCO 1. Participants expressed firm preference for integrated modern mechanisms into the Net-metering program, effective transition of energy models, establishing consumer engagement and discretion, proactive financial management, and commercial arrangements. The findings emphasized the financial liability PELCO 1 faces due to its Net-metered consumers, and the notable regulatory and operational gaps of the program. This study provided viable recommendations aimed to safeguard the utility against advancements of the program while promoting balanced compliance with policy requirements. By addressing these identified challenges PELCO 1 could significantly enhance its adoption of the Net-metering program and acquire a refined financial framework.